2022
DOI: 10.3390/w14010098
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Minimum Night Flow Estimation in Water Distribution Networks and Comparison with the Water Balance Approach: Large-Scale Application to the City Center of Patras in Western Greece

Abstract: Quantification of water losses (WL) in water distribution networks (WDNs) is a crucial task towards the development of proper strategies to reduce them. Currently, WL estimation methods rely on semi-empirical assumptions and different implementation strategies that increase the uncertainty of the obtained estimates. In this work, we compare the effectiveness and robustness of two widely applied WL estimation approaches found in the international literature: (a) the water balance, or top-down, approach introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…In doing so, we use the EPANET solver (see [84,85]) for hydraulic modeling of water distribution and resilience estimation, and hierarchical clustering enriched with topological proximity constraints (see [75]) for the delineation of PMAs. Before proceeding with the implementation of the algorithm, it is essential to estimate the water equilibrium of the analyzed water system (see Section 2 and Table 2) using, e.g., the recently developed probabilistic minimum night flow (MNF) estimation methodology introduced by Serafeim et al [4,20]. Figure 2 presents a flow chart of the developed algorithmic steps that were applied to the four largest PMAs of the water distribution network of the city of Patras (see Figure 1), as detailed in Sections 3.1-3.4 below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In doing so, we use the EPANET solver (see [84,85]) for hydraulic modeling of water distribution and resilience estimation, and hierarchical clustering enriched with topological proximity constraints (see [75]) for the delineation of PMAs. Before proceeding with the implementation of the algorithm, it is essential to estimate the water equilibrium of the analyzed water system (see Section 2 and Table 2) using, e.g., the recently developed probabilistic minimum night flow (MNF) estimation methodology introduced by Serafeim et al [4,20]. Figure 2 presents a flow chart of the developed algorithmic steps that were applied to the four largest PMAs of the water distribution network of the city of Patras (see Figure 1), as detailed in Sections 3.1-3.4 below.…”
Section: Methodsmentioning
confidence: 99%
“…As outlined in the Introduction, in order to manage and reduce leakages in water distribution networks, one needs to first estimate their volume as a percentage of the System Input Volume (SIV). To do so, we used the results obtained by Serafeim et al [20]. The latter study compared the water loss estimates obtained by applying the water balance (or top-down) approach, and the bottom-up approach based on the MNF estimation method from Serafeim et al [4], to the aforementioned four PMAs (i.e., Boud, Kentro, Panahaiki and Prosfygika).…”
Section: Data and Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Serafeim et al [72,[110][111][112][113][114][115] studied the minimum night flow (MNF) in pressure management areas (PMAs), revealing that that in PMAs with considerable leakage levels, the MNF estimates increase almost linearly with increasing inlet pressure.…”
Section: Pressurementioning
confidence: 99%
“…There are also other methods to estimate water loss, such as modified minimum night flow (MNF) and component analysis, which include the Burst and Background Estimate (BABE) methods [ 18 , 19 ]. While Serafeim et al [ 20 ] reported that estimated water losses by the MNF and BABE methods converge when rigorous statistical analysis is performed, MNF requires intensive field work, and the estimated night consumption are rarely accurate [ 18 ].…”
Section: Introductionmentioning
confidence: 99%